Faktor-Faktor Yang Mempengaruhi Kecanduan Game Online Peserta Didik - Sapto Irawan; Dina Siska W. (JURNAL KONSELING GUSJIGANG, 2021)
The purpose of this study was to determine the factors that influence online game addiction in students at SMA Negeri 1 Kuaro. Using descriptive quantitative research. The data collection adopted from the questionnaire Muhammad Reyzal Almujahid (2016). The research subjects in this study were students at SMA Negeri 1 Kuaro with a sample size of 64 students. Based on the results of the overall data analysis, the indicator of the frequency of playing online games obtained an average percentage of 33.57% so that it can be categorized as addiction to playing online games for students at SMA Negeri 1 Kuaro including in the moderate category. Overall, the indicator of time to play online games obtained an average percentage of 34.46% so that it can be categorized as addiction to playing online games of students at SMA Negeri 1 Kuaro in the moderate category, and overall indicators of games or games that are popular are obtained a mean percentage of 31.97% so that it can be categorized as addiction to playing online games of students at SMA Negeri 1 Kuaro in the moderate category.